Reinterpretation of the effective elastic thickness in terms of Young’s modulus variation applying the analytical solution for an Elastic Plate (ASEP) to the Barents Sea - Wienecke S.; Ebbing J.; Kukowski N.; BRAITENBERG, CARLA (American Geophysical Union, 2006)
We apply the analytical solution for an elastic plate (ASEP), which solves the 4th order differential equation for the flexure of a thin plate to the Barents Sea in order to calculate the flexural rigidity. To constrain our analysis we make use of a 3D density model based on the Barents50 model [Ritzmann et al. 2006]. The density model provides information about the crustal configuration, e.g. the Moho and the loading in the crust including all internal density variation. The loading in combination with the ASEP allows us to calculate the flexure Mohos, and by comparison with the reference Moho, the flexural rigidity distribution. The resulting flexural rigidity distributions will be used to validate tectonic concepts, e.g. the location of the proposed Caledonian suture. In the past the effective elastic thickness (EET) has been used synonymously for the flexural rigidity, since it was defined by the material parameters of Young's modulus and Poisson ratio, which were assumed to be constant. The application of the ASEP shows, that it is sufficient to operate with a constant value for the Poisson's ratio, as the variation does not lead to a significant change in the result. However, concerning the vertical and horizontal variation of crustal composition, which corresponds to a change of Young modulus by orders of magnitude - the use of a constant standard value in the calculation process is doubtful. For that reason the EET distribution was recalculated including the Young's modulus variation, which could be estimated by using the p- wave velocities of the Barents50 model. From the viewpoint of solid-state physics the elastic thickness concept should be reconceived. The EET corresponds theoretically to a thickness of a flexed plate, which consists of a material describable by a constant Young's modulus. Therefore the obtained EET distribution could be related to a Young's modulus variation, if the calculation was done with a constant assumed standard value. If the crust and the upper mantle have a non-uniform ...